ANALYSIS OF APPLICATION OF CHARACTER VALUES OF NATIONAL SPIRIT, LOVE FOR THE COUNTRY, AND RESPECT FOR ACHIEVEMENT IN CLASS V STUDENTS OF SD INPRES 4 BIROBULI - Wayan Sudarsana; Sesilia Tri Utami; Ni Ketut Puriani; Metz Violita (STAH Dharma Sentana Sulawesi Tengah, 2023)
This research aims to determine the application of the character values ​​of national spirit, love of the country, and respect for the achievements of class V students at SD 4 Inpres Birobuli. The type of research used is descriptive quantitative using interview data collection techniques and student questionnaires. Based on the results of processed descriptive data from 24 students who were respondents, it was stated that the application of character values ​​with very good criteria was 3 respondents or 12.5%, for good criteria there were 9 respondents or 37.5%, while for good criteria there were 9 respondents or 37.5%, sufficient criteria and not having a good number of respondents. The same, namely 6 respondents each or 25%. So it can be seen from the description above that the application of the character values ​​of national spirit, love of the country, and respect for the achievements of class V students at SD 4 Inpres Birobuli is relatively good.